The Crimean moment and crucible: Ideas of war and peace, 1854-6 - Spanou, P (2022)
Disrupting an almost forty-year period of peace in Europe, the Crimean War (1854-6) led Victorians to the belief that they were living through an historic caesura. Besides intensifying extant moral and ideological divisions within Victorian society, this conflict also exposed the horrors of the battlefront in graphic detail, and so acquired an unprecedented degree of immediacy and visibility. ‘Seeing’ war in all its fearful reality gave rise to challenging moral questions. This thesis argues that the Crimean War thus became a crucible in which Victorians negotiated and contested ideas of war and peace. Within a wider ‘war’ of words and ideas, peace advocates and their critics fiercely debated the morality of wars in general, and the justice of the Crimean War in particular. At the same time, Victorians reflected seriously and more deeply than at any time over the previous decades on war’s place in the life of a professedly Christian nation. Where many historians have studied the war intensively as an episode in diplomatic and military history, this thesis advances fresh perspectives on its unique impact on Victorian thought and culture, by tracing the complex ways in which the idea of ‘just war’ and the principles of the peace movement framed religious, intellectual, political, and cultural debates. It is distinctive in developing a wide contextual perspective, and in placing diverse commentators—churchmen, dissenters, historians, parliamentarians, poets, writers, artists, and others—within a common argumentative framework. Offering a close, critical, and analytical reading of an eclectic range of underused and hitherto untapped sources, it uncovers the remarkable cross-fertilization of various motifs between them, and illuminates the interactivity of debate. The result is an account that reconstructs a richer and more holistic picture of ideas and debates about a war which marked a defining moment in the Victorian era.